Leadership Coaching: Are We Missing the Alchemy? - Forbes, Raymond L. (Advances in Social Sciences Research Journal, 2022)
In an era characterized by fear, uncertainty and doubt Leadership Coaches now find themselves operating on more difficult and unfamiliar terrain. Enabling their clients to cope, survive and thrive in such tenuous conditions offers a significant professional challenge. This paper offers an unusual supplemental approach to more conventional and traditional coaching methods. Utilizing principles derived from the ancient field of alchemy, as well as from modern neuroscience, this article provides both new ideas and guidance to the practitioner of leadership coaching. Beginning with a guided imagery, this piece will then cover the connection between alchemy and leadership, followed by alchemy’s relationship to leadership coaching. The article will next review some relevant findings from contemporary brain science focusing, in particular, on the role of the unconscious mind. The ensuing section provides some ideas for what Leadership Coaches might consider doing differently to be more effective in working with their clients. The article concludes with a short summary and discussion of future implications.